Qualidade, translucidez e metabolismo antioxidante de infrutescências do abacaxizeiro ‘pérola’ sob adubação nitrogenada e potássica. - Lima, Renato Pereira (2016)
Practices for pre-harvest management in the pineapple crop (Ananas comosus var. comosus), such as the mineral fertilizer, can improve the quality of the crop at harvest and reduce the initial levels of translucency, which change the color of the pulp and leads to internal browning. These practices may also influence the production of hydrogen peroxide (H2O2) and antioxidants content. However, in relation to nitrogen fertilization and potassium these effects are not well characterized, yet. Based on that, this research is divided into two experiments. Primarily aimed to assess the quality and translucency infructescenses pineapple 'Pérola' produced under nitrogen and potassium fertilization. In the second, aimed at evaluating changes in antioxidant metabolism and H2O2 content in inflorescences of pineapple 'Pérola' in nitrogen and potassium fertilization. Five urea doses (0.53; 3.20; 5.33; 7.47; 10.13) and five of potassium chloride (0.30; 1.78; 2.97; 4.15; 5.64) were combined in a factorial as the Plan Puebla III matrix, totaling ten treatments, with three replicates in RBD. It was found that nitrogen and potassium fertilization in the cultivation of pineapple 'Pérola' influence translucency levels in the flesh of inflorescences, the commercial maturity. In this context, high-dose N (7.47 g urea per plant) combined with low K (1.78 g KCl per plant) increases the color of the pulp and reduces the content of flavonoids yellow. However, the translucency reduced when K was given at a dose of 4.15 g KCl per plant with 7.47 g of urea per plant. Thus, the combination of 7.47 g urea 4.15 g KCl per plant in the cultivation of pineapple 'Pérola' favors the quality of the seed heads, maintaining the low levels of translucency and high brightness values (L*) of the pulp , yellow flavonoids content, reducing sugars and soluble proteins in the pulp and core. In turn, the digital imaging proved to be an important tool in the characterization of translucency and changes in pulp color associated with this phenomenon. In the second study, it was noted that low doses of N and K, and the excess of such nutrients individually, increased the H2O2 content and therefore the activity of antioxidant enzymes. The catalase activity increased especially when K was high and N reduced, while the superoxide dismutase, ascorbic acid peroxidase and peroxidase increased when both were low or too high. In this condition, the content of ascorbic acid and total extractable polyphenols were also high and provided higher total antioxidant activity. On condition that the experiment was carried out, the combination of 5.33 g urea 2.97 g KCl per plant, the fertilization of pineapple 'Pérola', promotes a balance between antioxidant metabolism and H2O2 levels in the pulp and core of inflorescences. In addition, a principal component analysis showed that N/K ratios are as important as the absolute concentrations of these nutrients in optimizing antioxidant metabolism and thus of these nutrients must not be considered separately.